Escape or Fight: Inhibitors in Hemophilia A - Merlin, Simone; Follenzi, Antonia (Frontiers in Immunology, 2020)
Replacement therapy with coagulation factor VIII (FVIII) represents the current clinical treatment for patients affected by hemophilia A (HA). This treatment while effective is, however, hampered by the formation of antibodies that inhibit the activity of infused FVIII in up to 30% of treated patients. Immune tolerance induction (ITI) protocols, which envisage frequent infusions of high doses of FVIII to confront this side effect, dramatically increase the already high costs associated with a patient’s therapy and are not always effective in all treated patients. Therefore, there are clear unmet needs that must be addressed in order to improve the outcome of these treatments for HA patients. Taking advantage of preclinical mouse models of hemophilia, several strategies have been proposed in recent years to prevent inhibitor formation and eradicate the pre-existing immunity to FVIII inhibitor positive patients. Herein, we will review some of the most promising strategies developed to avoid and eradicate inhibitors, including the use of immunomodulatory drugs or molecules, oral or transplacental delivery as well as cell and gene therapy approaches. The goal is to improve and potentiate the current ITI protocols and eventually make them obsolete.